Pengaruh Content Marketing dan Social Media Influencer terhadap Brand Awareness - Eca Ayu Pratama; Ajeng Aquinia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the extent to which Content Marketing and Social Media Influencers influence the level of Brand Awareness of Emina products among consumers. This study was conducted using a survey method on 100 respondents who were familiar with and had used Emina products. The sampling technique used was purposive sampling, and the primary data was analyzed using SPSS. The results of this study indicate that both Content Marketing strategies and Social Media Influencers have a positive and significant impact on Brand Awareness, particularly among the 17-30 age group. Based on the research findings, it can be concluded that marketing strategies involving digital content and collaborations with social media influencers are effective approaches in enhancing Emina's Brand Awareness.